Co-Seismic Surface Ruptures of the CE 1738 M 7.6 Dangjiang Earthquake Along the NW Continuation of the Xianshuihe Fault Zone and Tectonic Implications for the Central Tibetan Plateau - Yu, Zhongyuan; Yin, Na; Xiao, Peng; Chen, Baixu (Frontiers in Earth Science, 2022)
The role of large-scale strike-slip faults in high-elevation areas in absorbing the strain resulting from plates convergence has yet to be scientifically understood. The Dang Jiang Fault (DJF), as the NW continuation of the Xianshuihe Fault zone (XFZ) in central Qinghai-Tibetan Plateau, may provide an excellent testing ground for this question, given its high slip rate, sparse vegetative cover, minimal modification, and possible relationship with CE 1738 Dangjiang destructive earthquake. However, the co-seismic surface ruptures and seismotectonics remain in dispute because of inconvenient transportation and lack of oxygen at high altitudes. Thus, field investigations are conducted here to determine the co-seismic co-seismic surface ruptures. The newly synthesized data from geologic observations, historical record reviews, geomorphic mapping, trench logging and sample dating indicate that the CE 1738 Dangjiang earthquake produced ~100 km-long surface rupture that includes offset of gullies, linear scarps and troughs, sag ponds, en echelon fractures and pressure ridges. Magnitude is re-estimated as Ms 7.6, with average and the maximum strike-slip displacements of ~2.1±0.1 m and ~3.5±0.1 m, respectively. The DJF has undergone multiple seismic faulting events, and the linear fitting surface displacement rate in the Holocene is ~6.3±1.9 mm/yr with a 95% confidence interval. The study implies that the seismic risk of the DJF cannot be underestimated given its elapsed time is close to or beyond the recurrence interval of major earthquakes, and that the oblique convergence of the Qiangtang Block might be accommodated by the clockwise rotation of block through the repeated left-lateral strike-slip movements along the southern boundary of the Bayan Har Block.